Empowering Women Through Mother Groups: A Case Study of Hanshposha Aama Samuha, Itahari- 20, Sunsari - Poudel, Tanka Mani (Dristikon: A Multidisciplinary Journal, 2021)
Empowering of women has become the major aspect of growth of the financial system of a country. It is basically the manner of enhancement of social, economic, cultural and political standing of women, the conventionally disadvantaged, neglected ones, in the society. This study has been carried out in Itahari sub-metropolitan, Sunsari district. The central theme of this study is to assess the role of Aama Samuha for empowerment of women and social development. This study entertains both primary as well as secondary data. The primary data have been collected from the field through survey Questionnaire, semi-structure interview, and observation. The interview was focused mainly on empowerment of women through mothers group, problems faced by the members of MG, while working in the group, attitude of males toward mothers group and role of mothers group in social development. Mothers Group of Hanshposha has contributed much in social development like cleaning trails, making road, plantation on public area, financial support to local school, and construction of building for temples, financial support to helpless people and poor people and maintaining peace and harmony in the community.